2016
DOI: 10.1016/j.chom.2016.07.019
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus pneumoniae Senses a Human-like Sialic Acid Profile via the Response Regulator CiaR

Abstract: Summary Streptococcus pneumoniae is a human-adapted pathogen that encounters terminally sialylated glycoconjugates and free sialic acid (Sia) in the airways. Upon scavenging by the bacterial sialidase NanA, Sia products serve as carbon sources for the bacteria. Unlike most animals in which cytidine-monophosphate-N-acetylneuraminic acid hydroxylase (CMAH) converts Sia N-acetylneuraminic acid (Neu5Ac) into N-glycolylneuraminic acid (Neu5Gc), humans have an inactive CMAH, causing an absence of Neu5Gc and excess N… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
34
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(36 citation statements)
references
References 65 publications
0
34
1
1
Order By: Relevance
“…The presence of various amounts of sialidase-resistant Sias may therefore contribute to selection of influenza virus populations with HA variants, while its display on some horse and guinea pig cells in culture may provide an in vitro system suitable for the study of this modified Sia and its interactions with influenza and other viruses. Little is known about the direct effects of 4-O-Ac Sia on other microbes and pathogens, but their effects on sialidase (neuramindase) function would likely alter susceptibility in many respiratory viral and bacterial pathogens ( 66 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…The presence of various amounts of sialidase-resistant Sias may therefore contribute to selection of influenza virus populations with HA variants, while its display on some horse and guinea pig cells in culture may provide an in vitro system suitable for the study of this modified Sia and its interactions with influenza and other viruses. Little is known about the direct effects of 4-O-Ac Sia on other microbes and pathogens, but their effects on sialidase (neuramindase) function would likely alter susceptibility in many respiratory viral and bacterial pathogens ( 66 68 ).…”
Section: Discussionmentioning
confidence: 99%
“…Sialic acid released by NanA has been shown to act as a signal, increasing bacterial loads in the nasopharynx of mice colonized with S. pneumoniae and facilitating invasion of nasal tissue and progression to pneumonia and meningitis 105,106 . Such signalling involves the two- transcriptional regulatory protein CiaR and requires sialic acid uptake by the transporter SatABC, and this results in increased pneumococcal resistance to antimicrobial reactive oxygen species 107 . NanA can also trigger TGFβ signalling pathways, leading to endothelial cell invasion 108 .…”
Section: Invasive Pneumococcal Diseasementioning
confidence: 99%
“…The milder phenotype of the hk11 H184A strain than that of rr11 D53A suggested that RR11 is phosphorylated by an alternative phosphoryl group donor(s) besides HK11. Hentrich et al reported that intracellular acetyl phosphate generated by pyruvate kinase SpxB is capable of phosphorylating the RR05 (CiaR) response regulator [50]. To elaborate on the function of HK11 in phase variation, we constructed a "hyper-active" mutant of HK11 by making a T-to-P mutation in the 190 th threonine residue.…”
Section: Phosphorylated Form Of Rr11 Drives Pneumococci Toward the Omentioning
confidence: 99%